2015
DOI: 10.1016/j.msea.2015.04.053
|View full text |Cite
|
Sign up to set email alerts
|

A critical examination of pure tantalum processed by high-pressure torsion

Abstract: Tantalum, a common refractory metal with body-centred cubic (BCC) crystalline structure, was processed by high-pressure torsion (HPT) at room temperature through different numbers of rotations. Significant grain refinement and high strength were achieved with a reduction in grain size from ~60 m to ~160 nm and an increase in strength from ~200 to >1300 MPa. Hardness measurements revealed a high level of homogeneity after 10 turns of HPT but the hardness after 10 turns was slightly lower than after 5 turns ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 59 publications
4
21
0
Order By: Relevance
“…6 show there is an increase from an initial value of ~260 to ~920 MPa after 10 turns but with a corresponding reduction in elongation from ~79% to ~29%. This strength and ductility paradox matches other reports for the HPT processing of an Al-1% Mg alloy [30] and pure tantalum [31] where it was shown that short-term annealing after HPT processing produced a small reduction in strength but a significant increase in ductility.…”
Section: Strength and Ductility Development During Hpt Processing Andsupporting
confidence: 91%
“…6 show there is an increase from an initial value of ~260 to ~920 MPa after 10 turns but with a corresponding reduction in elongation from ~79% to ~29%. This strength and ductility paradox matches other reports for the HPT processing of an Al-1% Mg alloy [30] and pure tantalum [31] where it was shown that short-term annealing after HPT processing produced a small reduction in strength but a significant increase in ductility.…”
Section: Strength and Ductility Development During Hpt Processing Andsupporting
confidence: 91%
“…In addition, annealing may also decrease the dislocation density in the grain interior of an SPD-processed material, thereby facilitating effective dislocation storage, and an enhanced storage capability may increase the strain hardening leading to increased ductility in these materials. Subsequently, similar results were reported for Cu processed by ECAP [37], Ti processed by ECAP and drawing [38], Ti processed by ECAP-Conform and drawing [39], and pure Ta processed by HPT [40].…”
Section: Effect Of a Short-term Anneal After Processingsupporting
confidence: 78%
“…In addition, short-term annealing reduces the dislocation density in the grain interior of the UFG material after SPD so that the dislocation storage capability may increase and thus the strain hardening capability is enhanced wand this leads to the possibility of high ductility in the SPD-processed material. There are several recent reports demonstrating the significance of PDA on mechanical properties at RT of HPT-processed materials [51][52][53][54]. Thus, considering the present nanoindentation results reporting a significant enhancement in the strain rate sensitivity after PDA, the MMNC in the Al-Mg system produced by HPT has a great potential for demonstrating both high hardness and superior ductility.…”
Section: The Improvement In Micro-mechanical Response By Pdasupporting
confidence: 57%